Booming tuition industry : reproducing social inequality in Singapore’s education system - Liow, Ruo Yu (2016)
The Singapore education system strictly observes meritocracy where it rewards students based on individual academic performance and effort. However, the existence of a widespread private tuition industry (commonly termed as shadow education system) is problematic as education, traditionally seen as a vehicle for social mobility, may prove to exacerbate the widening social inequality in Singapore. While the structural-functionalist perspective asserts that a meritocratic education system rewards people based on merit and not birth, conflict theorists draw attention to how socioeconomically advantaged families can now purchase additional ‘help’ in participating in high stakes examinations. This paper explores the reasons for Singapore’s “minor national obsession” with tuition and how social inequalities are reproduced by the tuition industry. The research also serve to provide new insights into the relationship between the education system and its largely ignored shadow.